Comparison of performance levels over 25 m by 11 expert swimmers using anguilliform-like and carangiform-like techniques; eel-like swimming versus carangiform-like swimming - Collard, L.; Auvray, E.; Bellaunay, I. (International Journal of Performance Analysis in Sport, 2011)
Performance levels over 25 m for two underwater swimming techniques (carangiform- and anguilliform-like swimming) were compared in 11 national-level, competitive swimmers. Several indicators of propulsive efficiency were recorded: leg oscillation frequency and amplitude, head oscillation amplitude and the Strouhal number (St). Video analysis suggested that head movement amplitude correlates with performance levels in anguilliform-like swimming (dolphin kicking with the arms alongside the trunk). However, analysis of St did not lead to the expected results in our evaluation of carangiform-like swimming (i.e. conventional dolphin kicking, with the arms stretched out in front). Although the anguilliform-like technique is not used in competitive swimming, it turned out to be as effective in our swimmers (despite the lack of prior practice) as the carangiform-like technique. This paper discusses the relevance of two techniques inspired by the animal kingdom and which are vying to become the "fifth stroke".